Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Dan Kinerja Guru Di Sd Negeri Kecamatan Gondang Mojokerto - Maya Sari, Fajar (Program Doktor Ilmu Ekonomi, 2013)
Teacher is the main staff in school, they are the main part of all activities, education and national teaching, whether for school and local society. Teacher is trusted by parents to educate their children. Through teacher, students will able to see the world with wider concept and through teacher, there also cultural transformation from generation to generation. Since teacher has important role in education process and human resources development, then effort will involve motivation and quality in order to get more achievement. The purpose of this research is finding out the influence of competence and working environment on teacher working satisfaction at State Elementary School in Gondang Sub District, finding out the influence of competence and working environment on teacher performance of State Elementary School in Gondang Sub District and finding out the influence of working satisfaction on teacher performance of State Elementary school in Gondang Sub District. Population of this research is all teachers of State Elementary School in Gondang Sub District which total is 182 peoples from 23 State Elementary School in Gondang Sub District. Analysis technique that being used in this research is SEM that tested by using AMOS 16 program. The result of this research shows that : (1) Competence and working environment has significant influence on teachers working satisfaction at State Elementary School in Gondang Sub District, (2) Competence and working environment do not have significant influence of teacher performance at State Elementary School in Gondang Sub District, (3) Working satisfaction has significant influence on teacher performance in State Elementary School in Gondang Sub District.Keywords : competence, working environment, working satisfaction, performance